Recent Insights into Electrochemical Sensing of Per- and Polyfluoroalkyl Substances - Christopher T. LeBarron; Pavithra; Seyyedamirhossein Hosseini (ECS Sensors Plus, 2025)
Per- and polyfluoroalkyl substances (PFAS) are widely studied due to their persistence, prevalence, and harmful effects on human and environmental health. Key challenges include improving detection methodologies, such as lowering detection limits, and developing more sensitive and selective approaches. Given the ubiquity of PFAS, effective sensing must be paired with remediation strategies that transform these pollutants into value-added or less toxic products. This perspective explores recent advances in electrochemical PFAS detection, highlighting challenges and future opportunities.